Penatalaksanaan Terapi Latihan Pasca Operasi Pemasangan Austin More Prothesis Pada Fraktur Collum Femur DextraDi RSO PROF. DR. Soeharso Surakarta - Fitria, Mareta Dwi; , Dwi Kurniawati, SST.Ft.,M.Kes (2015)
Background: femoral neck fracture is a fracture that occurs in colum femoris. This fracture is one type of fracture is greatly affect the quality of human life. Objective: To determine the management of Exercise therapy can reduce pain, reduce edema, increase muscle strength and improve ADL in post-operative conditions of the installation of more prothsis austin on dextra femur collum. Results: Reduction of pain silent Tl = 3 becomes T3 = 1, pain motion T1 to T3 = 6 = 4 and tenderness T1 to T3 = 4 = 2. There is an increasing range of motion in the hip active LGS S = 00-0-200 T1 to T3 S = 100-0-250, T1 to T3 300-0-00 F = F = 350-0-00, LGS knee T1 S = 00-0-250 into T3 S = 00-0-300, LGS ankle T1 to T3 S = S = 200-0-400 200-0-450. LGS passive hip 00-0-250 fixed T1 S = S = 00-0-250, T1 F = 350-0-00 remain T3 F = 350-0-00, LGS knee T1 S = 00-0-350 fixed T3 S = 00-0-350, LGS ankle T1 S = 200-0-450 remain T3 = S = 200-0-450.Atropometri major Trocantor decrease edema distal 10cm to 68cm becomes T1 = T3 = 65cm, major trocantor kedistal 20cm kedistal T1 to T3 = 59cm = 52cm, 30cm kedistal major trocantor = 41cm T1 to T3 = 41.Panjang limbs do not experience leg length discrepancy. The ability of functional activity, an increase in the ability of functional activity. Methods: A case study in which patients studied and observed progress during therapy three times. Conclusion: Various problems that arise in the post-operative conditions of the installation of more prothsis austin on femoral neck fractures this dextra Exercise therapy is used to solve the problem, namely ankle excercise, exercise pelvic muscle contraction, ressisted, hold relax, Quadriceps strengthening exercises, exercises sitting, Exercise standing edge of bed, walking exercises. the implementation of the exercise therapy results obtained for pain reduction, decrease edema, meningtan muscle strength, increase LGS, upgrading functional activity.